2020
DOI: 10.1111/1756-185x.13777
|View full text |Cite
|
Sign up to set email alerts
|

The direct and indirect costs of axial spondyloarthritis (axSpA) in Singapore

Abstract: Objective To estimate the economic annual direct and indirect costs of axial spondyloarthritis (axSpA) in Singapore, and to identify factors associated with these costs. Methods A retrospective, cross‐sectional, Institutional Review Board‐approved study was conducted. A questionnaire was administered to the patients between 2013 and 2016 from the Singapore General Hospital (SGH) spondyloarthritis registry. Direct medical costs and indirect costs were estimated using the SGH database and the human capital appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Economic modelling of axSpA has thus far focused on the indirect costs of reduced patient productivity in the workplace. 19 , 41 , 42 A study conducted across three European countries estimated the mean annual societal direct costs for each patient were EUR 2640, with worse physical function and higher disease activity as important determinants of cost. 43 More specifically, a study carried out in the United Kingdom estimated the annual cost of workplace absenteeism and presenteeism per patient with axSpA was GBP 411 and GBP 3425, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Economic modelling of axSpA has thus far focused on the indirect costs of reduced patient productivity in the workplace. 19 , 41 , 42 A study conducted across three European countries estimated the mean annual societal direct costs for each patient were EUR 2640, with worse physical function and higher disease activity as important determinants of cost. 43 More specifically, a study carried out in the United Kingdom estimated the annual cost of workplace absenteeism and presenteeism per patient with axSpA was GBP 411 and GBP 3425, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, indirect costs such as work disability and household work contribute significantly to the disease burden [ 16 ]. As the disease primarily affects young people in the productive age range, indirect costs stemming from work absenteeism and decreased productivity due to functional limitations in patients play a pivotal role [ 17 , 18 , 19 ]. A Brazilian study revealed that nearly 59% of the study group was retired or on leave from work as a result of the disease [ 18 ].…”
Section: Introductionmentioning
confidence: 99%